Construing the Challenges and Opportunities of Intercultural Language Teaching Amid Covid-19 Pandemic: English Teachers' Voices - Ahmad Sugianto; Nadya Ulfah (Yayasan Visi Intan Permata, 2020)
Due to globalization, intercultural competence becomes one of the prominent competences in English teaching. Unfortunately, the current condition, the COVID-19 pandemic happened may not lead the intercultural language teaching run as expected because it should be moved to an online setting. Through combining qualitative and quantitative research methods with questionnaires and interviews, this study aimed to unravel the teachers' competence and the challenges and opportunities of intercultural language teaching during the current situation. This study concluded that most of the teachers' intercultural competence was deemed moderate. Furthermore, some challenges found comprised the aspects of internet access and students' psychological aspect, such as attitudes toward intercultural language teaching and learning conducted in an online classroom. Meanwhile, the opportunities found comprised the aspect of language skills, attitudes, and the other supporting skill such as critical thinking development.